A revision of the Dibrachys cavus species complex (Hymenoptera: Chalcidoidea: Pteromalidae) - Peters, Ralph S.; Baur, Hannes (Zootaxa, 2011)
The taxonomy and host ranges of the cavus species complex within Dibrachys Förster (Chalcidoidea: Pteromalidae) are revised. Examination of about 810 specimens, including multivariate morphometric analysis of 21 quantitative characters clearly separated three species, Dibrachys microgastri (Bouché, 1834), Dibrachys lignicola Graham, 1969, and Dibrachys verovesparum Peters & Baur sp. n., but allowed no further subdivision of taxa according to origin, host association or previous taxonomic concepts. A neotype is designated for D. microgastri and under this name are placed in synonymy the names Dibrachys cavus (Walker, 1835) syn. n. (including eight current junior synonyms), Dibrachys clisiocampae (Fitch, 1856) syn. n. (including five current junior synonyms), Dibrachys boarmiae (Walker, 1863) syn. n., and Dibrachys elegans (Szelényi, 1981) syn. n. Dibrachys goettingenus Doganlar, 1987 syn. n. is synonymized under D. lignicola. The morphological analyses revealed several new qualitative and quantitative characters for separating taxa in this species complex and an identification key and diagnoses are provided for females and males. Dibrachys microgastri is a polyphagous generalist pupal ectoparasitoid of several different orders of holometabolous insects, whereas D. lignicola is a polyphagous ectoparasitoid of hosts in Diptera, Lepidoptera and Hymenoptera, and D. verovesparum is a primary or secondary parasitoid in nests of Vespidae.